Percolation implications in the rheology of polymer crystallization. Issue 2 (26th October 2020) - Kotula, Anthony P.; Migler, Kalman B.
Abstract: The rheology of polymer crystallization is an old problem that often defies explanation due to the complex interrelationships between crystallization and flow properties. Although separate measurements of rheology and crystallinity can give some information on their relationship, it is only through simultaneous measurements that ideas on the rheology of polymer crystallization can be tested and developed. This Perspective details recent experimental developments in simultaneous crystallinity and rheology measurements as well as continuum modeling efforts for the case of quiescent and isothermal crystallization. Experimental results reveal that the rheology is dominated initially by growth of individual spherulites that evolve into spherulitic superstructures that eventually span the measurement geometry. A generalized effective medium model based on this concept of percolation can explain both the growth of the viscoelastic modulus during crystallization and the changes in the relaxation spectrum of the crystallizing polymer, including a critical gel response at percolation. The success of the combined measurement techniques and percolation concepts motivate research to extend the semicrystalline polymer materials space where these methods are applied as well as further develop novel techniques to gain additional insight into the evolution of structure and relaxation dynamics during crystallization. Abstract : How does a polymer transition from a molten, flowable melt to a viscoelastic solid? This Perspective details efforts to answer that question via novel measurements and an effective medium model. Simultaneous crystallinity and rheology measurements indicate that spherulites are a dominant rheology modifier, which directly affects conceptual thinking regarding semicrystalline polymer processing and crystallizing polymer rheology.